Evaluating Household Transmission of Invasive Group A Streptococcus Disease in the United States Using Population-based Surveillance Data, 2013–2016. (13th August 2019) - Adebanjo, Tolulope; Apostol, Mirasol; Alden, Nisha; Petit, Susan; Tunali, Amy; Torres, Salina; Hollick, Rosemary; Bell, Austin; Muse, Alison; Poissant, Tasha; Schaffner, William; Van Beneden, Chris A
Abstract: Using population-based surveillance data, we quantified the secondary invasive group A Streptococcus disease risk among household contacts. The disease risk in the 30 days postexposure to an index-case patient was highest among individuals aged ≥65 years, versus the annual background incidence of all ages.